Age decreases mitochondrial motility and increases mitochondrial size in vascular smooth muscle. (9th April 2016) - Chalmers, Susan; Saunter, Christopher D.; Girkin, John M.; McCarron, John G.
Abstract : Key points: Age is proposed to be associated with altered structure and function of mitochondria; however, in fully‐differentiated cells, determining the structure of more than a few mitochondria at a time is challenging. In the present study, the structures of the entire mitochondrial complements of cells were resolved from a pixel‐by‐pixel covariance analysis of fluctuations in potentiometric fluorophore intensity during 'flickers' of mitochondrial membrane potential. Mitochondria are larger in vascular myocytes from aged rats compared to those in younger adult rats. A subpopulation of mitochondria in myocytes from aged, but not younger, animals is highly‐elongated. Some mitochondria in myocytes from younger, but not aged, animals are highly‐motile. Mitochondria that are motile are located more peripherally in the cell than non‐motile mitochondria. Abstract: Mitochondrial function, motility and architecture are each central to cell function. Age‐associated mitochondrial dysfunction may contribute to vascular disease. However, mitochondrial changes in ageing remain ill‐defined because of the challenges of imaging in native cells. We determined the structure of mitochondria in live native cells, demarcating boundaries of individual organelles by inducing stochastic 'flickers' of membrane potential, recorded as fluctuations in potentiometric fluorophore intensity (flicker‐assisted localization microscopy; FaLM). In freshly‐isolated myocytes from rat cerebral resistance arteries, FaLM showed a range of mitochondrial X‐Y areas in both young adult (3 months; 0.05–6.58 μm 2 ) and aged rats (18 months; 0.05–13.4 μm 2 ). In cells from young animals, most mitochondria were small (mode area 0.051 μm 2 ) compared to aged animals (0.710 μm 2 ). Cells from older animals contained a subpopulation of highly‐elongated mitochondria (5.3% were >2 μm long, 4.2% had a length:width ratio >3) that was rare in younger animals (0.15% of mitochondria >2 μm long, 0.4% had length:width ratio >3). The extent of mitochondrial motility also varied. 1/811 mitochondria observed moved slightly (∼0.5 μm) in myocytes from older animals, whereas, in the younger animals, directed and Brownian‐like motility occurred regularly (215 of 1135 mitochondria moved within 10 min, up to distance of 12 μm). Mitochondria positioned closer to the cell periphery showed a greater tendency to move. In conclusion, cerebral vascular myocytes from young rats contained small, motile mitochondria. In aged rats, mitochondria were larger, immobile and could be highly‐elongated. These age‐associated alterations in mitochondrial behaviour may contribute to alterations in cell signalling, energy supply or the onset of proliferation. Key points: Age is proposed to be associated with altered structure and function of mitochondria; however, in fully‐differentiated cells, determining the structure of more than a few mitochondria at a time is challenging. In the present study, the structures of the entire mitochondrial complements of cells were resolved from a pixel‐by‐pixel covariance analysis of fluctuations in potentiometric fluorophore intensity during 'flickers' of mitochondrial membrane potential. Mitochondria are larger in vascular myocytes from aged rats compared to those in younger adult rats. A subpopulation of mitochondria in myocytes from aged, but not younger, animals is highly‐elongated. Some mitochondria in myocytes from younger, but not aged, animals are highly‐motile. Mitochondria that are motile are located more peripherally in the cell than non‐motile mitochondria.